Calcium‐overloaded sympathetic preganglionic neurons in a case of severe sepsis with anorexia nervosa. Issue 3 (15th December 2014) - Kinebuchi, Miyuki; Matsuura, Akihiro
Abstract : Aim: We aimed to show the status of intracellular elements in sympathetic preganglionic neurons in an autopsy case of a 55‐year‐old woman with severe sepsis and cardiac dysfunction with anorexia nervosa. Methods: Our methods include a case report and pathological examinations of autopsied tissues using synchrotron‐generated microbeam X‐ray fluorescence analysis. Results: A case report of severe sepsis and myocardial dysfunction. The patient had sudden short cardiac arrest without arrhythmia and sequelae, and echocardiogram showed negative inotropic change. The X‐ray fluorescence analysis of autopsied tissues indicated an unusually high concentration of cytosolic calcium in sympathetic preganglionic neurons. However, there were no significant pathological findings of damage in the heart or the cardiovascular autonomic nuclei in the central nervous system. Conclusion: The data indicate that dysfunction of the sympathetic preganglionic neurons exists in a patient of severe sepsis and cardiac dysfunction with anorexia nervosa.